Log in to add a comment

## Answers

My answer is P=1/2 To get it, I subtracted the second term and the 1st term.

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

1) Find the difference between each term:

a) (P + 5) - (3P + 2)

= (P + 5) + (-3P - 2) - To subtract polynomial, change the signs of eacht

term in subtrahend, then proceed to addition

=

b) (3P + 2) - (P + 3)

= (3P + 2) + (-P - 3)

=

2) Equate the difference between the terms, since this is an arithmetic sequence where the difference between each term is equal.

To check,

P + 3 = 1 + 3 =

Arithmetic sequence:

a) (P + 5) - (3P + 2)

= (P + 5) + (-3P - 2) - To subtract polynomial, change the signs of eacht

term in subtrahend, then proceed to addition

=

*-2P + 3, difference between third and second terms*b) (3P + 2) - (P + 3)

= (3P + 2) + (-P - 3)

=

**2P - 1, the difference between second and first terms**

2) Equate the difference between the terms, since this is an arithmetic sequence where the difference between each term is equal.

**2P - 1 = -2P + 3****2P + 2P = 3 + 1****4P = 4****4P/4 = 4/4**

__P = 1__To check,

**substitute 1 for P:**P + 3 = 1 + 3 =

**3P + 2 = 3(1) + 2 = 3 + 2 =***4*

*P + 5 = 1 + 5 =***5**

**6**

Arithmetic sequence:

*Common difference:***4, 5, 6**

**1**